A CASE STUDY OF CODE SWITCHING IN SCHOOLCHILDREN'S UTTERANCES IN THE MULTILINGUAL COMMUNITY - Anggraeni, Diah (2015)
The present study seeks to investigate the phenomenon of code switching among schoolchildren in the multilingual community. Data were taken from 26 schoolchildren from two different age groups. The first group consists of 16 children whose age range from 8 to 9 years old, and the second group consists of 10 children whose age range between 10 to 11 years old. Data were analyzed qualitatively supported by descriptive quantification and based on Poplack's (1980) and Reyes' (2004) code switching theories. In addition, the interview guideline and analysis to find children's perspectives in this study were adapted from Vasquez (2009). The findings show that the most typical code switching type that occur in the schoolchildren's utterances is intra-sentential switching, and the specific intention in the children's code switching are insistence, emphasis, clarification, question shift, discourse marker and other similar reasons which is related to social purposes. Moreover, in the multilingual setting, this study supports the previous study result proposed by Pradina, Soeriasoemantri and Heriyanto (2013) that code switching can be used as a communicative strategy among children. However, the children see code switching as the indication of the second language incompetence. Penelitian ini bertujuan untuk menganalisa fenomena alih kode pada anak-anak dwibahasa Indonesia Inggris di sebuah komunitas. Data diperoleh dari 26 anak sekolah yang berasal dari dua kelompok yang berbeda. Kelompok kesatu terdiri dari 16 anak yang berusia 8 hingga 9 tahun, dan kelompok kedua terdiri dari 10 anak yang berusia 10 hingga 11 tahun. Data dianalisa secara kualitatif dengan bantuan kuantifikasi secara deskriptif dan teori Poplack (1980) dan Reyes (2004). Selain itu, pedoman wawancara dan analisis dalam penelitain ini diadaptasi dari studi Vasquez (2009). Hasil penelitian menunjukan bahwa tipe alih kode yang paling sering digunakan oleh anak-anak adalah intra-sentential switching, dan fungsi utama menggunakan alih kode adalah sebagai insistence, emphasis, clarification, question shift, discourse marker, dan fungsi lainnya yang berkaitan dengan fungsi sosial. Selain itu, penelitian ini membuktikan hasil penelitian sebelumnya yaitu penelitian Pradina, Soeriasoemantri dan Heriyanto (2013) yang mengemukakan bahwa alih kode dapat digunakan sebagai strategi komunikasi diantara anak-anak dwibahasa. Meskipun demikian, pada latar dwibahasa, anak-anak melihat alih kode sebagai indikasi dari ketidakcakapan bahasa kedua.